DISTOPIA KONDISI LIBERALISME DALAM FILM TIGA (Studi Semiotika Roland Barthes Tentang Distopia Liberalisme di Jakarta dalam Film Tiga) - Tuty Mutiah; Dhefine Armelsa; Faqihar Risyan; Agung Raharjo (Universitas Bina Sarana Informatika, 2019)
Dystopia in Film Tiga Liberalism Conditions (Roland Barthes Semiotics Studies about Dystopia on Liberalism in Jakarta in Film Tiga). This study goals is to determine the meaning of dystopian condition of Jakarta in the Film Tiga through the sign, signifier and signified. Three films is a film that adopts Liberal describe the depravity of Jakarta twenty years in the future in 2036. The method used semiotic analysis of Roland 2 Bartes.The object of research is the Film Tiga were directed by Anggy Umbara and classified through five objects dystopia condition of Jakarta, dystopian condition of the state apparatus, dystopia conditions of religion, dystopia technology, and dystopias journalism to find signs and markers and meaning at the level of the first and second, the denotation, connotations and myths.These results indicate that the situation of Jakarta transformed into an increasingly metropolis marked by the increasing number of high-rise buildings, as well as demonstrations marked depicted in 2015 until 2025. In 2026, the revolution ended and became State Liberalism. Changes in the State apparatus are characterized by the wish to dominate the world to create freedom in the face of the earth. One is to get rid of religion, by damaging the face of religion. State Officials do havoc with bring into conflict of the Religion. Changes religion marked by shifting religious values, is marked by religion becomes a thing wrong choice. The lack of freedom is depicted in this film, must be eradicated in order to function in a Liberal to be ideal. Technological changes are interpreted as changes in technology that convey information quickly, as well as the ability to hacked That meaning is characterized by technological devices that undergo changes such as, mobile phones, flash, televisions, doors, computers, laptops and so forth is now transformed into transparent. The changes meant the journalistic agenda setting media that is still happening characterized by lack of freedom of the press.